Colonial interference in the translations of the Bible in Southern Sotho - Makutoane, T. J.; Naudé, J. A. (Acta Theologica, 2009)
Bible translation in South Africa was initially conceptualised and executed by either missionary societies or Bible societies. This paper aims to investigate the nature of the translators’ encounters and negotiations between the source text culture and the culture of the target audience. For purposes of this study, the translation of cultural terms of two translations of the Bible into Southern Sotho will be considered. The first translation to be discussed was published in 1909 by the Paris Evangelical Missionary Society representing colonial empowerment of the dominated target culture by the hegemonic culture of the translators. The second translation discussed was published in 1989 by the Bible Society of South Africa. It represents a process of indigenisation of the source text culture.